2012
DOI: 10.1002/adma.201200436
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Control of Protein Conformation

Abstract: Conducting polymer devices that enable precise control of fibronectin conformation over macroscopic areas are reported. Single conformations as well as conformation gradients are achieved by applying an appropriate potential. These surfaces remain biologically relevant and support cell culture; hence, they may serve as a model to understand and control cell-surface interactions, with applications in basic research, medical diagnostics, and tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 26 publications
(26 reference statements)
3
97
0
2
Order By: Relevance
“…A gradient in the surface potential was established by applying ±1.0 V across the electrode while the electrode was incubated for 1 h in cell culture medium containing Fn (Figure 6c and 6d). [190] …”
Section: Electroactive Nanomaterials For Electrode-tissue Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…A gradient in the surface potential was established by applying ±1.0 V across the electrode while the electrode was incubated for 1 h in cell culture medium containing Fn (Figure 6c and 6d). [190] …”
Section: Electroactive Nanomaterials For Electrode-tissue Interfacesmentioning
confidence: 99%
“…c,d) Reproduced with permission. [190] Copyright 2012, Wiley-VCH. e) SEM images at 15,000×magnification of NGF entrapped in PEDOT films compared with control films produced without NGF modification of the electrolyte.…”
Section: Figurementioning
confidence: 99%
“…6 Moreover, the cyto-compatibility of PEDOT:PSS has enabled its use in various in vivo and in vitro platforms. 7,8 In particular, previous reports showed that 2D thin films of PEDOT:tosylate, a similar conducting polymer, could electrochemically control protein conformation, 9 and cell secretions. 10 In recent years, several different strategies have been employed to develop porous PEDOT-based materials for applications in sensing, power supply, capacitance, and electrical storage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 3T3-L1 fibroblast-adipose cells deposited on a PEDOT:tosylate polymer that had a potential bias of -1V to +1V distributed with a preference for cell adhesion toward the positive bias end. It was found that the amount of protein adsorption decreased 18,19 but had a greater propensity to adopt a more unfolded conformation 20 along the gradient toward the positive bias end of increased cell adhesion. A similar effect was observed with neural stem cells on a PEDOT:tosylate electrode with a 2-fold increase in cell adhesion on the oxidized polymer even though the protein adsorption was lower compared to the reduced polymer 21 .…”
Section: Introductionmentioning
confidence: 99%
“…surface potential and conductivity) 29,30 , that have been shown to display nanoscale lateral variation are expected to amplify variations in the conformation and adhesion of individual proteins across the polymer surface. Whilst the above studies have focused on conformation 17,20,21 , the FN-polymer interfacial forces are also interest as they play an important role in force-dependent signal transduction processes such as cellular forces exerted on FN through cell receptors and intracellular proteins to regulate cell function.…”
Section: Introductionmentioning
confidence: 99%